Pengaruh Edukasi Menggunakan Media Power Point Terhadap Pengetahuan Dan Sikap Tentang Kecacingan Pada Anak Di Sdn 89 Kota Bengkulu Tahun 2025 - Kristina Elvira; Emi Pebriani; Meri Epriana Susanti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Helminthiasis is an infectious disease caused by Soil-Transmitted Helminths (STH) parasites and remains a health problem for elementary school-aged children. Worm infections can impact nutritional status, reduce immunity, and affect children's concentration and academic achievement. One preventative measure is through health education using engaging learning media such as PowerPoint presentations to increase knowledge and foster positive attitudes about helminthiasis prevention. The method used was a quantitative study with a pre-experimental design using a One Group Pretest-Posttest design. The study was conducted at SDN 89 in Bengkulu City, with a sample of 46 respondents drawn using a total sampling technique. Data were collected using a knowledge and attitude questionnaire, then analyzed univariately and bivariately using the Wilcoxon test. The results of the univariate analysis showed that before the education, the majority of respondents (30 respondents (65.2%) had a positive attitude and 16 (34.8%) had a negative attitude, with a median of 27. After the education, the median increased to 32. The knowledge variable also saw an increase in the mean and median scores between the pre-test and post-test. The Wilcoxon test yielded a p-value of 0.000 (p<0.05), indicating a significant effect of education using PowerPoint media on students' knowledge and attitudes about helminthiasis at SDN 89, Bengkulu City, in 2025. It is recommended that schools and health workers optimize the use of PowerPoint media or other visual media in providing health education to increase understanding and encourage clean and healthy living behaviors in students.